Facile Preparation of Linear Polyurethane from UPy‐Capped Poly(dl‐Lactic Acid) Macrodiol. Issue 1 (8th November 2018) - Ren, Wei; Li, Zhenlong; Chen, Yimei; Gao, Hanyang; Yang, Wei; Wang, Yuanliang; Luo, Yanfeng
Abstract: Linear polyurethanes based on poly(dl ‐lactic acid) (PDLLA) macrodiol are promising materials in tissue engineering, yet their synthesis requires rigorous control on various parameters. A facile way to prepare linear polyurethanes by capping the PDLLA macrodiol ( M n  = 4536) with 2‐ureido‐4[1 H ]‐pyrimidone (UPy) is reported. The obtained low‐molecular‐weight UPy‐capped polyurethane can form flexible, stretchable, and hydrophobic supramolecular films due to the strong and unidirectional quadruple hydrogen bonding of UPy dimers. Tensile tests, shape recovery, and self‐healing observations indicate that, compared with conventional PDLLA macrodiol‐based linear polyurethane ( M n  = 48840 and PDI = 1.8), the UPy‐capped polyurethane films have comparable mechanical properties (tensile modulus: 900 ± 38 MPa; ultimate strength: 9.6 ± 0.8 MPa) yet significantly better shape memory and self‐healing properties. These results suggest that the UPy‐capped polyurethane might become an alternative for conventional linear polyurethane as a new biomedical material. Abstract : A facile way to prepare linear polyurethanes is introduced by capping macrodiol with UPy units. The obtained low‐molecular‐weight polyurethane can form flexible and hydrophobic supramolecular films and demonstrates comparable mechanical properties yet significantly better shape memory and self‐healing properties than the conventional high‐molecular‐weight linear polyurethane.